2020
DOI: 10.1097/corr.0000000000001285
|View full text |Cite
|
Sign up to set email alerts
|

Is a Short-course of Preoperative Denosumab as Effective as Prolonged Therapy for Giant Cell Tumor of Bone?

Abstract: Background Denosumab is an inhibitor of monoclonal receptor activator of nuclear factor-ĸB ligand, approved to treat giant cell tumors of bone (GCTB). It is commonly used for unresectable tumors and for downstaging the tumor to perform less-morbid procedures. Although denosumab has been used extensively for GCTBs, there are no recommendations regarding the duration of therapy. The risk factors associated with local recurrence (LR) in patients receiving preoperative denosumab for GCTB also are unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…92,93 Denosumab, a human monoclonal antibody to receptor activator of nuclear factor kappa B (RANK)-ligand (RANK-L), known to be overexpressed in GCTB, is the standard treatment in unresectable or metastatic GCTBs [III, A]. [93][94][95] Its use in the preoperative setting for GCTBs that are potentially resectable with high morbidity is debated and should be reserved for complex cases [II, C]. 96 There is increasing evidence that, if used preoperatively and before curettage, surgery is best carried out after a few months of J o u r n a l P r e -p r o o f treatment, although the most appropriate length of preoperative treatment has not been established yet [V, C].…”
Section: Giant Cell Tumour Of Bonementioning
confidence: 99%
See 1 more Smart Citation
“…92,93 Denosumab, a human monoclonal antibody to receptor activator of nuclear factor kappa B (RANK)-ligand (RANK-L), known to be overexpressed in GCTB, is the standard treatment in unresectable or metastatic GCTBs [III, A]. [93][94][95] Its use in the preoperative setting for GCTBs that are potentially resectable with high morbidity is debated and should be reserved for complex cases [II, C]. 96 There is increasing evidence that, if used preoperatively and before curettage, surgery is best carried out after a few months of J o u r n a l P r e -p r o o f treatment, although the most appropriate length of preoperative treatment has not been established yet [V, C].…”
Section: Giant Cell Tumour Of Bonementioning
confidence: 99%
“…96 There is increasing evidence that, if used preoperatively and before curettage, surgery is best carried out after a few months of J o u r n a l P r e -p r o o f treatment, although the most appropriate length of preoperative treatment has not been established yet [V, C]. 93,94 The optimal schedule and duration of treatment with denosumab in metastatic or surgically unsalvageable GCTs is also undefined, and the possible long-term side-effects are still largely unknown. Preliminary evidence suggests that denosumab interruption can be followed by disease progression.…”
Section: Giant Cell Tumour Of Bonementioning
confidence: 99%
“…Maximum 3–4 months was deemed as the optimum time frame before intralesional surgery, considering that 6 months made the possibility of recurrence rate higher by getting the bony shell thicker and trapping more tumor cells. Hindiskere et al ( 51 ) found that there were no significant differences between short-course (there or fewer doses) and long-course (more than three doses) groups of preoperative denosumab in terms of clinical scores, histological and radiological response or local recurrence survivorship. Short-course could reduce costs and complications linked with long-course therapy.…”
Section: Denosumab May Increase the Risk Of Local Recurrence In Patiementioning
confidence: 99%
“…Hindiskere et al analyzed 161 patients with GCTB who received preoperative denosumab treatment for downstaging prior to surgery. They reported that there was no difference between short-term and long-term administration of denosumab in terms of radiologically objective tumor response (90 % [43 of 48] vs. 81 % [29 of 36]; p = 0.24), histological response (79 % [38 of 48] vs. 83 % [30 of 36]; p = 0.81), and local recurrence-free survival rate at five years after surgery (73 % vs. 64 %; p = 0.50) [ 10 ]. They suggested that reducing the preoperative dose of denosumab can reduce the complications and costs of denosumab [ 10 ].…”
Section: Main Textmentioning
confidence: 99%
“…They reported that there was no difference between short-term and long-term administration of denosumab in terms of radiologically objective tumor response (90 % [43 of 48] vs. 81 % [29 of 36]; p = 0.24), histological response (79 % [38 of 48] vs. 83 % [30 of 36]; p = 0.81), and local recurrence-free survival rate at five years after surgery (73 % vs. 64 %; p = 0.50) [ 10 ]. They suggested that reducing the preoperative dose of denosumab can reduce the complications and costs of denosumab [ 10 ]. These studies suggest that physicians should carefully consider the use of denosumab before curettage of GCTB, and confirm that a short course of denosumab before resection can make surgery easier, with a lower risk of local recurrence.…”
Section: Main Textmentioning
confidence: 99%